Delay in diagnosis among sputum smear positive tuberculosis patients in Kuching, Sarawak - Deburra, Peak Ngadan. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Tuberculosis (TB) is a global problem, and the incidence of TB in Malaysia has been above the target of less than 40 per 100,000 population since the past 15 years (1995-2010). TB control strategies have been implemented and strengthened including directly observed treatment, short course (DOTS), BCG vaccination, early detection, treatment and contact tracing. However, the challenge remains in early diagnosis and prompt treatment, contributed by an increase in patient delay duration and health system delay duration. This research study used a cross-sectional survey toexamine the rate of delay duration in diagnosing sputum smear positive pulmonary TB (PTB) patients in Sarawak.